Review of Diagnostic Tests for Detection of Mycobacterium bovis Infection in South African Wildlife - Bernitz, Netanya; Kerr, Tanya J.; Goosen, Wynand J.; Chileshe, Josephine; Higgitt, Roxanne L.; Roos, Eduard O.; Meiring, Christina; Gumbo, Rachiel; de Waal, Candice; Clarke, Charlene; Smith, Katrin; Goldswain, Samantha; et al. (Frontiers in Veterinary Science, 2021)
Wildlife tuberculosis is a major economic and conservation concern globally. Bovine tuberculosis (bTB), caused by Mycobacterium bovis (M. bovis), is the most common form of wildlife tuberculosis. In South Africa, to date, M. bovis infection has been detected in 24 mammalian wildlife species. The identification of M. bovis infection in wildlife species is essential to limit the spread and to control the disease in these populations, sympatric wildlife species and neighboring livestock. The detection of M. bovis-infected individuals is challenging as only severely diseased animals show clinical disease manifestations and diagnostic tools to identify infection are limited. The emergence of novel reagents and technologies to identify M. bovis infection in wildlife species are instrumental in improving the diagnosis and control of bTB. This review provides an update on the diagnostic tools to detect M. bovis infection in South African wildlife but may be a useful guide for other wildlife species.